Design, Synthesis and Biological Evaluation of Rose Bengal Analogues as SecA Inhibitors. Issue 8 (21st June 2013) - Cui, Jianmei; Jin, Jinshan; Hsieh, Ying‐Hsin; Yang, Hsiuchin; Ke, Bowen; Damera, Krishna; Tai, Phang C.; Wang, Binghe
Abstract SecA, a key component of bacterial Sec‐dependent secretion pathway, is an attractive target for exploring novel antimicrobials. Rose bengal (RB), a polyhalogenated fluorescein derivative, was found from our previous study as a potent SecA inhibitor. Here we describe the synthesis and structure–activity relationships (SAR) of 23 RB analogues that were designed by systematical dissection of RB. Evaluation of these analogues allowed us to establish an initial SAR in SecA inhibition. The antimicrobial effects of these SecA inhibitors are confirmed in experiments using E. coli and B. subtilis.